(3EOGQI GdYedjGJ GdeUQajI GdeMdjI hGdeUQajIs - (3NGdO Cejf(B, (3YHO Gddgs; (3GSeGYjd GHQGgje(B, (3GdWQGOs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2006)
(3GdJYQja HGdLgGR GdeUQaj(B- (3GdYedjGJ GdeUQajI GdeMdjI(B- (3GdYedjGJ GdeUQajI GdNGQLjI(B- (3GdJehjd GdOhdj(B.s
Keywords: (3GdEOGQIs; (3GdeUGQas